Implementation of a speckle-based spectrometer - Ugarte La Torre, Diego Renato (2016)
There are different methods to measure light wavelength. One of these methods is based on the relationship between wavelengths and speckle patterns. The original implementation of this method used a multimode optical fiber to generate speckle patterns. To test if this method still operates appropriately when it uses a different source of speckle patterns, this work proposes an implementation in which the multimode optical fiber is replaced by a liquid crystal display (LCD). Our results show that it is possible to implement the method with a LCD. The use of a LCD reduces the mechanical instability and improves the reproducibility of the generated speckle patterns.